The complete mitochondrial genome of Callionymus olidus (Perciformes Callionymidae). Issue 1 (2nd January 2021) - Liu, Yanshan; Wang, Yanping; Yin, Jiawen; Li, Daming; Tang, Shengkai; Gu, Xiankun; Zhang, Tongqing; He, Haoran; Zhu, Binqing
Abstract: In this study, we present the complete mitogenome and a phylogenetic analysis of Callionymus olidus, determined by long PCR and primer walking methods. The complete mitochondrial genome is a circular molecule of 16, 491 bp in length and contains the same set of 37 mitochondrial genes (13 protein-coding genes, 2 ribosomal RNA (rRNA), 22 transfer RNA (tRNA)), and a control region as other bony fishes. The base composition of the entire mitogenome showed a slight excess of AT bias. The entire mitogenome data produced in this study provides the genomic resources available for future evolutionary studies.